ROR1 sustains caveolae and survival signalling as a scaffold of cavin-1 and caveolin-1 - Tomoya Yamaguchi (Nature Portfolio, 2016)
Resistance to receptor tyrosine kinase inhibitors is a major obstacle in treatment of lung adenocarcinoma. Yamaguchi et al.identify the orphan receptor ROR1 as a potential target to overcome this resistance, by virtue of its role in promoting cell survival through stabilisation of caveolae.